PENGEMBANGAN PERANGKAT PEMBELAJARAN MENGGUNAKAN MODEL PEMBELAJARAN GUIDE INQUIRY BERBASIS “QAIT” PADA MATA KULIAH STRUKTUR ALJABAR I MATERI GRUPOIDA - Restu Lusiana; Tri Andari (IKIP PGRI MADIUN, 2014)
The aims of this research is to create a good learning tools of Algebra Stucture towards “QAIT”based Guide Inquiry. Algebra Stucture as basic subject in mathematics. This conditions isessensials for students to comprehend the materials. The using of “QAIT” based Learning Model Guide Inquiry is one of the ways to incrase motivation student on learning. “QAIT” based Learning Model Guide Inquiry will increase the active learning of the students. This developmental researchwas applying Thiagarajan's,et al. 4D developmental approach. Thiagarajan's approach consisted of 4D phases approaches. The phases are Define, Design, Development and Disseminate. The population was students of fifth semester of Mathematics Department of IKIP PGRI Madiun. The datacollections techniques used were in form of test and non-test (questionnaire). The results were collected from the approach's trial. Learning tools already stated valid and has good criteria on students' effective activities, lecturer's classroom management, sensitiveness of students' results test, validity, reliability, and students' positive responses. Good learning tools of Algebra Stucture towards “QAIT”based Guide Inquiry creates (1) Satuan Acara Pembelajaran (SAP), (2) Lembar Kegiatan Mahasiswa (LKM), (3) Tes Hasil Belajar (THB) of Spatial-n Euclides of Linear Algebra.